Nurses are leaving the nursing profession: A finding from the willingness of the nurses to stay in the nursing profession among nurses working in selected public hospitals of Wollega Zones, Oromia, Ethiopia. (March 2022) - Mulisa, Diriba; Tolossa, Tadesse; Oluma Ayana, Adugna; Regasa, Misganu Teshoma; Bayisa, Lami; Abera, Tesfaye; Mosisa, Alemnesh; Wakuma, Bizuneh; Etafa, Werku; Tsegaye, Reta; Fetensa, Getahun; Turi, Ebisa; et al.
Background: The willingness of nurses to stay in nursing profession is nurses stay in the nursing profession without having intention to shift their works to other professions. In healthcare systems, nurses are currently leaving their work. To give quality of health, nurses have to stay in their work. The aim of this study was to find the willingness of the nurses to stay in the nursing profession and associated factors. Methods: An institution-based cross-sectional study was employed among nurses in selected hospitals. After checking for completeness, the data were interred into Epi Data version 3 and exported to Stata SE version 14 for analysis. Then, the descriptive statistics were computed. To find association, logistic regression was computed. Covariates from binary logistic regression were a candidate for multivariate logistic regression at p -value ⩽ 0.25. Variables in the final model were selected by the stepwise backward selection procedure. In the end, variables with a p -value ⩽ 0.05 were considered as statistically significant. Results: In this study, 349 nurses have participated with a 100% response rate and more than half of the participants were male 188 (53.87%). The proportion of nurses who have the willingness to stay in the nursing proportion is 54.44% (95% confidence interval = 0.491, 0.59). Getting relatively high salary (adjusted odd ratio = 1.81 (95% confidence interval = 1.05, 3.11)), no presence of support among colleagues (adjusted odd ratio = 0.10 (95% confidence interval = 0.05, 0.22)), not having participation in training (adjusted odd ratio = 0.49 (95% confidence interval = 028, 0.86)), having relative low experience in nursing profession that is less than 6 years (adjusted odd ratio = 0.46 (95% confidence interval = 0.26, 1.81)), having good autonomy in the nursing profession (adjusted odd ratio = 0.41 (95% confidence interval = 0.23, 0.70)), and having a good sense of self-calling for the nursing profession among nurses (adjusted odd ratio = 2.85 (95% confidence interval = 1.64, 4.97)) are the factors related with willingness of the nurses to stay in the nursing profession. Conclusion and recommendation: To bring development in the nursing profession, it is a must to staying experienced nurses in the nursing profession. Therefore, to increase the willingness of nurses in the nursing profession, it is better to increase the salary of nurses, giving frequent training for the nurses, initiate the nurses to support one another, and encourage the nurses to have sense of self-calling for nursing profession. This is accomplished if there is a harmonious relationship between the governments, nurses, and other stakeholders in the healthcare delivery system.